Evaluation of potential substrates for biogas production in colombia using anaerobic digestion systems (2023)
Increasing energy demands around the globe require alternative sources of energy. Considering the large amount of agro-industrial and agriculture-related activities in Colombia, energy generation from biomass waste is a promising option to meet the energy needs of the country. Anaerobic digestion (AD) is a good alternative to use these wastes. In this study, several potential substrates for biogas generation using AD systems were identified through a literature review. Vinasses, palm oil industry residues, swine manure, coffee industry residues, and municipal solid wastes were found as potential substrates for AD. Considering factors such as composition, the amount of waste production, availability, and their relationship with important Colombian economic activities, three substrates were selected to perform biochemical methane potential (BMP) experiments. The selected substrates were swine manure (SM), palm oil mill effluent (POME), and coffee residues (CR). The obtained BMP values were 240, 465, and 314 NmLCH4/g VS, respectively. An analysis of kinetic parameters analysis was conducted for the BMP experiments, based on the logistic and Gompertz models. It was seen that the AD of SM starts faster than in the other evaluated substrates. Nevertheless, the overall methane production rate was the highest for POME, followed by CR. SM had the lowest methane production yield. The obtained values of BMP, kinetic parameters, and those collected during the literature review can be useful for the design and implementation of AD systems in Colombia. Moreover, attention should be paid to substrates such as POME, which have a high energy production potential.